2017
DOI: 10.1155/2017/1928171
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Triple Quadrupole Mass Spectrometry Analysis and Vasorelaxant Effect of Essential Oil fromProtium heptaphyllum(Aubl.) March.

Abstract: The Protium heptaphyllum species, also known as Almécega, produces an oily resin, used in folk medicine as an analgesic and anti-inflammatory agent, in healing, and as an expectorant, which is rich in pentacyclic triterpenes and essential oils. In this study, the essential oil obtained by hydrodistillation of Almécega's resin was analyzed by gas chromatography-triple quadrupole mass spectrometry and evaluated for chemical composition and vasorelaxant activity in rat superior mesenteric artery. The main constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(23 reference statements)
1
3
0
4
Order By: Relevance
“…To our knowledge, this is the first report showing the qualitative and quantitative analyses of VOCs from PHR by using solvent extraction, while all previous investigations showed the qualitative percentage of volatiles in PHR essential oil. However, the present data on VOC content in PHR oleum resin confirm the previously published reports, regarding which monoterpenes are the main chemical constituents of volatile fraction in the range between the 85% and the 98% [9,21,22]. The higher percentage of monoterpenes in the analyzed PHR samples were α-pinene (24.85%), p-cymene (21.85%), 3-carene (13.90%), β-phellandrene (13.33%) and α-phellandrene (8.30%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the first report showing the qualitative and quantitative analyses of VOCs from PHR by using solvent extraction, while all previous investigations showed the qualitative percentage of volatiles in PHR essential oil. However, the present data on VOC content in PHR oleum resin confirm the previously published reports, regarding which monoterpenes are the main chemical constituents of volatile fraction in the range between the 85% and the 98% [9,21,22]. The higher percentage of monoterpenes in the analyzed PHR samples were α-pinene (24.85%), p-cymene (21.85%), 3-carene (13.90%), β-phellandrene (13.33%) and α-phellandrene (8.30%).…”
Section: Discussionsupporting
confidence: 92%
“…In previously published studies, p -cymene and β-phellandrene were reported as the main volatile constituents of P. heptaphyllum essential oil (13.63% and 60.68% respectively) [ 21 ], whereas α-pinene and α-phellandrene were reported among the most abundant VOCs in essential oil reaching the 10.5% and the 16.70%, respectively, with terpinolene (28.50%) and limonene (16.9%) as main compounds [ 9 ]. The compound 3-carene was also reported among the characteristic P. heptaphyllum monoterpenes in essential oil (4.00%) from mechanically wounded tree [ 23 ] and commercial resin (5.11%) [ 22 ]. Few sesquiterpenes were reported in literature on P. heptaphyllum essential oil: β-( E )-caryophyllene was reported in two previously published reports at the percentage of 1.5% and 1%, respectively [ 9 , 11 ], whereas other notable reported sesquiterpenes were α-ylangene at 0.47% [ 21 , 23 ], α-cubebene (3.30%) [ 11 ] and α-gurjunene (0.30%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…EOPH from Ceará (Brazil) presented lower amount of monoterpenes (86.4%), and terpinolene (28.5%) was the main constituent, followed by α -pinene (10.5%) and α -phellandrene (16.7%) [15]. Mobin et al [2] reported the main constituents of EOPH determined by gas chromatography-triple quadrupole mass spectrometry were limonene, p -cineole, and o -cymene. In the EOPH from Acre (Brazil), twenty-one constituents (98.53%) were identified, and p -cymene (39.93%) was the main constituent followed by n-tetradecane (13.38%), dihydro-4-carene (11.69%), and α -phellandrene (7.41%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…is a tree which belongs to the Burseraceae family that produces an amorphous and aromatic resin with pharmacological activities in nervous and immunological systems and gastrointestinal tract [1]. In addition, it is used in folk medicine as an analgesic and anti-inflammatory agent, in healing, and as an expectorant, which is rich in pentacyclic triterpenes and essential oils [2].…”
Section: Introductionmentioning
confidence: 99%
“…Os componentes majoritários das resinas velhas (comercial) foram os monoterpenos limoneno, 1,8-cineol e p-cimeno, enquanto nas resinas frescas foram o limoneno, p-cimeno e α-terpineol. O óleo de resinas velhas mostrou ainda efeito vasorelaxante em bioensaios com ratos, sugerindo uma possível forma de tratamento alternativo para hipertensão (Mobin et al, 2017).…”
Section: Resultsunclassified